PERBEDAAN KADAR ENDOTELIN-1 PADA WANITA DIABETES MELLITUS TIPE 2 DENGAN DAN TANPA HIPERTENSI - , dr. Enita R Kurniaatmaja; , dr. Hemi Sinorita, SpPD-KEMD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. Hypertension and have a strong predisposition on the incidence of atherosclerosis. The incidence of hypertension is two times greater in patients with DM than non DM. Endothelial dysfunction underlies these events. Endothelial markers, endothelin-1 is known affect to affect blood pressure. The aims of this study is to determine the difference levels of endothelin-1 in type 2 diabetes mellitus women with and without hypertension. The subjects were divided into two groups, type 2 DM woman with hypertension groups and without hypertension. ELISA Methods. Cross sectional design was conducted on women with type 2 diabetes mellitus with and without hypertension at metabolic and endocrinology clinic, Dr. Sardjito General Hospital Yogyakarta. sandwichâs method was used to measure plasma levels of endothelin-1. Characteristics of the study are presented in the form of mean and standard deviations. The difference between groups were compared by studentâs unpaired t-test an Mann Whitney test. The P value is considered significant if p<0,05 with 95% confidence interval. Conclusion. From this study we expected to know the difference mean levels of endothelin-1 in women with type 2 diabetes with and without hypertension. The levels of endothelin-1 in type 2 DM woman with hypertension higher than those without hypertension